2019
DOI: 10.1104/pp.19.00591
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Hydraulic Failure Hypothesis of Esca Leaf Symptom Formation

Abstract: Vascular pathogens cause disease in a large spectrum of perennial plants, with leaf scorch being one of the most conspicuous symptoms. Esca in grapevine (Vitis vinifera) is a vascular disease with huge negative effects on grape yield and the wine industry. One prominent hypothesis suggests that vascular disease leaf scorch is caused by fungal pathogen-derived elicitors and toxins. Another hypothesis suggests that leaf scorch is caused by hydraulic failure due to air embolism, the pathogen itself, and/or plant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 52 publications
(52 reference statements)
4
42
0
Order By: Relevance
“…GLSD, characterized by tiger stripe-like symptoms on the leaves, is the most common expression of the disease [ 3 , 44 ]. ESCA-associated fungi are undetected in the distal organs of the vines (i.e., annual stems and leaves), demonstrating that vascular occlusions and symptoms occur at a distance from the pathogen niche localized in the wood [ 2 ]. Exhaustive research has shown that losses in grape yield and quality caused by ESCA are correlated with leaf symptom severity [ 34 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GLSD, characterized by tiger stripe-like symptoms on the leaves, is the most common expression of the disease [ 3 , 44 ]. ESCA-associated fungi are undetected in the distal organs of the vines (i.e., annual stems and leaves), demonstrating that vascular occlusions and symptoms occur at a distance from the pathogen niche localized in the wood [ 2 ]. Exhaustive research has shown that losses in grape yield and quality caused by ESCA are correlated with leaf symptom severity [ 34 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plant cell represents a complex of molecules combined with numerous additional components. Plant growth and development depends on the interaction between these components and environmental stimuli, such as pathogen attacks [ 1 , 2 , 3 , 4 ]. Plant response to pathogens is complex and composed of at least two layers: A basal, broad-band immunity called pathogen-associated molecular pattern-triggered immunity and a strain-specific level of immunity known as effector-triggered immunity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants were then classified by their long-term symptomatology record: plants asymptomatic from 2012 to 2018 (pA, previously asymptomatic), and plants that have expressed symptoms at least once between 2012 and 2018 (pS, previously symptomatic). The uprooting method and greenhouse growth conditions are detailed in Bortolami et al (2019).…”
Section: Plant Materialsmentioning
confidence: 99%
“…While the pathogens responsible for esca-induced trunk necrosis have been identified (Morales-Cruz et al, 2018;Brown et al, 2020), the underlying mechanisms of leaf and fruit symptoms, and plant death are still poorly understood. Bortolami et al (2019) demonstrated that the two vascular pathogens related to esca (Phaeomoniella chlamydospora and Phaeoacremonium minimum) were never detected in leaves or in one-year old stems, but always in the trunk (independently from leaf symptom presence). They further showed that esca symptomatic leaves presented significant losses in hydraulic conductivity due to the occlusion of the xylem conduits by tyloses.…”
Section: Introductionmentioning
confidence: 99%